Characterization and identification of twelve-tone composers - Costa, Lucas F. P.; Coca S., Andrés E. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2018)
The individualism of each composer is shaped in an inherent way to his personality, aiming for recognition of particular form through the own songs. In this way, it is possible to categorize a musical subgenre at a deeper level by identifying the composer from his works. However, the characteristics of each composer are so varied that they are difficult to identify. In this paper it is proposed to use machine learning to classify works of twelve-tone music according to the composer, under the hypothesis that in choosing the twelve-tone series a part of his signature was reflected. Experimental results showed promising performance and confirmed the existence of a relation between composer and series.